PENGGUNAAN THE SNAKES AND LADDERS GAME UNTUK MENINGKATKAN KEMAMPUAN ENVIRONMENTAL LITERACY SISWA SEKOLAH MENENGAH PERTAMA - Siti Sanisah; Ratnah Ratnah; Nurin Rochayati; Fauzan Fauzan; Sirajuddin Sirajuddin; Sri Rejeki (Universitas Hamzanwadi, 2025)
The edutainment approach is an integration of learning with games that can make learning more interactive and student-centered. This study aims to analyze the use of the Snakes and Ladders game to improve environmental literacy in class VIII students at SMP Negeri 5 Jonggat. The research used the Classroom Action Research (PTK) method, which was conducted in three cycles, each consisting of planning, implementation, observation, and reflection stages. The results showed an increase in learning outcomes in the pretest stage of 53, cycle I (55.75), cycle II (74.25), cycle III (84.25), and post-test reached 85.25, with a total increase of 32.25 points. It can be concluded that the use of snakes and ladders games is effective in improving students' environmental literacy skills. It is recommended that game development includes a variety of challenges and more complex interactive elements, expanding game content, and the implementation of the game is optimally accompanied by the teacher to ensure maximum student involvement and the creation of meaningful learning.